Contradictions of Financial Capital Switching: Reading the Corporate Leverage Crisis through The Port of Liverpool's Whole Business Securitization. (27th February 2020) - Ward, Callum
Abstract: David Harvey argued there to be an animating tension at the heart of the geographical dynamics of capital: a simultaneous need for both spatial fixity and perpetual motion. I adapt this frame for an era of financial globalization, arguing that fixity has been overcome through a 'quaternary circuit' of credit‐mediated capital switching which undermines the distinct roles of the three circuits Harvey identified. However, rather than resolving the fixity/motion contradiction, this has instead given it intensified form as capital liquidity versus spatial fixity. I explore this through the Port of Liverpool's innovative 'whole business securitization', tracing out the logic of leverage underpinning financial capital switching and how such practices transform the spatiotemporality of circulation while fostering the conditions for greater crises. By theorizing financial globalization from a capital switching perspective, this article combines Minskian and micro‐founded approaches to understanding investment chains in a way that reprises geographical political economy's critique of the territoriality of capitalist crisis.